(untitled) (PUSA Journal of Hospitality and Applied Sciences, 2022)
Background: Emotional intelligence has become a buzz word; Emotional Quotient (EQ) has long overtaken the Intelligence Quotient (IQ). A manager capable of recognizing and managing emotions of the self and of others may be more adept at work. Hoteliers have to work long hours due to which staff may become disgruntled and when insufficient returns are received, it may show up in their behaviour at work. The hotel industry is a service oriented industry which has an intangible product to sell, something that is produced and consumed in the same instant. Objectives: To understand in depth, the concept of emotional intelligence in hospitality. To analyze the link between EI and its role in developing effective leaders in hospitality. Methodology: Convenience sampling was used and the samples were approached online due to COVID. The samples were shortlisted from the personal contacts of the authors in Hyderabad’s 5 star hotels holding management level positions. Out of 50-60 samples approached, 43 samples consented for their inclusion. Results: EQ has been ignored in hospitality curriculum with 55% sample base completely agreeing to and same should be for hiring, as voted by all 43 samples. 26 samples were also in complete favor of EI being a necessary pre-requisite for promotions. Conclusion: EI is extremely necessary in leader building and developing EI focused course for the under-graduates will help inculcate the quality in later stages of career.